Production of probiotic-fortified composite poultry feed from food and agricultural waste material (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of the study was to ascertain the feasibility of fortifying composite poultry feed from food and agricultural waste material with the probiotic organism Lactobacillus fermentum and determine the efficiency of formulated probiotic-fortified feed via animal feeding tests.Materials and Methods: Probiotic-fortified feed (G3) was formulated using proximate analysis values of waste materials. Alternative diets were G1—Feed Mill of Nigeria starter mash and G2—Ground corn. For growth comparison test, 30 1-day-old Agricol broiler chicks were randomized into three groups of 10 chicks each with each group being placed on a separate diet (G1, G2, and G3). Probiotics antimicrobial efficacy feeding assay consisted of the treatment diets T1—Feed Mill of Nigeria starter mash and T2—probiotic-fortified feed. Twenty 1-day-old unvaccinated chicks were placed into two groups of 10 chicks each and fed 0.5 ml of 9.0 × 108 CFU/ml Escherichia coli 0157:H7 on day 1 after which they were placed on treatment diets. Data collected were analyzed and interpreted using the SPSS Statistical tool version 25.Results: Chicks fed G1 and G3 diets performed similarly (p < 0.05) in terms of measured parameters (weight, height, and wingspan) and had better performance compared to chicks on G2. In the E. coli treatment group, chicks placed on treatment diets T1 and T2 showed similar levels of E. coli cell reduction every week. Performance based on measured parameters was also similar (p < 0.05).Conclusion: Feasibility of fortifying composite animal feed with the probiotic organism L. fermentum was ascertained and the efficiency of the feed via animal feeding tests was proven.J. Adv. Vet. Anim. Res., 6(4): 544-548, December 2019